Pregnant Mother Assistance in Utilizing the Maternal and Child Health Book (KIA) in the Tanah Kali Kedinding Kenjeran Surabaya Public Health Center Area - Sherly Jeniawaty; Sukesi; Rekawati (Community Empowerment in Health, 2023)
Utilization of the Maternal and Child Health Book (KIA Book) that is not yet optimal can result in lowcoverage of benefits and completeness of content. Efforts to improve the coverage of KIA Bookutilization include providing assistance on how to fill in and utilize the KIA Book for pregnant mothers.The partner for this activity is pregnant mothers in the Tanah Kali Kedinding Public Health Center,Kenjeran District, Surabaya. This activity is a community service conducted through focused groupdiscussions. The activity has increased the knowledge of pregnant mothers by 92.5% regarding theutilization of the KIA Book. The coverage of completeness in filling the KIA Book has reached 100%. Itcan be concluded that this activity has successfully improved the knowledge of pregnant mothersregarding the utilization of the KIA Book, and the pregnant mothers are committed to using the KIABook as a communication and educational tool.